Fiber-Enhanced Raman Sensing of Cefuroxime in Human Urine - Yan, Di; Frosch, Timea; Kobelke, Jens; Bierlich, Joerg; Popp, Juergen; Pletz, Mathias W.; Frosch, Torsten (Analytical Chemistry, 2018)
Fiber-enhanced Raman spectroscopy was developed for the chemically selective and sensitive quantification of the important antibiotic cefuroxime in human urine. A novel optical sensor fiber was drawn and precisely prepared. In this fiber structure, light is strongly confined in the selectively filled liquid core, and the Raman scattered signal is collected with unprecedented efficiency over an extended interaction length. The filling, emptying, and robustness are highly improved due to the large core size (>30 μm). Broadband step-index guidance allows the free choice of the most suitable excitation wavelength in complex body fluids. The limit of detection of cefuroxime in human urine was improved by 2 orders of magnitude (to μM level). The quantification of cefuroxime was achieved in urine after oral administration. This method has great potential for the point-of-care monitoring of antibiotics concentrations and is an important step forward to enable clinicians to rapidly adjust doses.
CRIS-Team Scopus Importer:2023-04-20